2017
DOI: 10.21873/anticanres.11757
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Importance of Vitamins A, E and Retinol-binding Protein 4 in Renal Cell Carcinoma Patients

Abstract: Low levels of vitamin A, E and RBP4 at the time of RCC diagnosis are associated with a poorer prognosis after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…For instance, Fei et al reported lower RBP4 serum levels in patients with colon cancer than in healthy individuals [17]; on the other hand, Karunanithi et al and Abola et alhave shown that elevated RBP4 is associated with colon cancer progression and liver metastasis [18,19]. There are also studies showing the importance of this protein in ovarian, renal, hepatocellular, oral squamous cell, and pancreatic cancer patients [20][21][22][23][24]. Such analyses conducted in patients with breast cancer suggested a link between elevated RBP4 and the risk of breast cancer [25].…”
mentioning
confidence: 99%
“…For instance, Fei et al reported lower RBP4 serum levels in patients with colon cancer than in healthy individuals [17]; on the other hand, Karunanithi et al and Abola et alhave shown that elevated RBP4 is associated with colon cancer progression and liver metastasis [18,19]. There are also studies showing the importance of this protein in ovarian, renal, hepatocellular, oral squamous cell, and pancreatic cancer patients [20][21][22][23][24]. Such analyses conducted in patients with breast cancer suggested a link between elevated RBP4 and the risk of breast cancer [25].…”
mentioning
confidence: 99%
“…A recent study revealed that RBP-4, which links obesity and cancer, is one of the pathogenic mechanisms of cancers, including prostate cancer, that is related to obesity (41), breast cancer (42), pancreatic cancer (43), and more. However, Sobotka et al (44) found that low levels of RBP-4 at the time of renal cellar cancer diagnosis are associated with poorer prognosis after surgery, and Lorkova et al (45) veri ed a decrease in RBP-4 levels in ovarian cancer patient sera by two independent methods.…”
Section: Discussionmentioning
confidence: 99%
“…The downregulation of this enzyme is also an adaptation of lipid metabolism in hypoxic cancer cells, which is mediated by HIF-1 [ 38 ]. Regarding retinol-binding protein 4, the low expression of Rbp4 has previously been associated with a poorer prognosis in patients with renal cell [ 41 ] and hepatocellular carcinomas [ 42 ] or breast cancer [ 43 ]. Interestingly, a recent single-cell sequencing study analyzing the differences between right- and left-sided colorectal cancer tissues revealed that the specific presence of a subpopulation of RBP4+ cancer cells in the latter was associated with a higher ratio of pre-exhausted/exhausted T cells and an increased responsiveness to immunotherapy [ 44 ].…”
Section: Discussionmentioning
confidence: 99%